An interview with Thomas J. Sargent - George W. Evans; Seppo Honkapohja (Center for Economic Studies and ifo Institute (CESifo), 2005)
The rational expectations hypothesis swept through macroeconomics during the 1970's and permanently altered the landscape. It remains the prevailing paradigm in macroeconomics, and rational expectations is routinely used as the standard solution concept in both theoretical and applied macroeconomic modelling. The rational expectations hypothesis was initially formulated by John F. Muth Jr. in the early 1960s. Together with Robert Lucas Jr., Thomas (Tom) Sargent pioneered the rational expectations revolution in macroeconomics in the 1970s. We interviewed Tom Sargent for Macroeconomic Dynamics.
Keywords: E00; 330; Rationale Erwartung; Wirtschaftswissenschaftler; Persönlichkeiten; Wissenschaft; Vereinigte Staaten; Sargent Thomas J.